MARKETING STRATEGY OF TAMAN ANYAR TOURIST ATTRACTION AS A CULTURAL EDUCATIONAL TOURISM IN PENARUNGAN TOURISM VILLAGE, MENGWI DISTRICT, BADUNG REGENCY - Anak Agung Any Sutraningrum; I Made Arsa Wiguna; I Gede Sedana Suci (Ride: Journal of Cultural Tourism and Religious Studies, 2024)
Penarungan Village offers several tourism potentials to visitors, including the Lazy River, Jogging Track, Beji Paluh Park, and Taman Anyar. The Taman Anyar Tourist Attraction has become one of the popular destinations for tourists visiting Penarungan Tourism Village, which positively impacts the local economy. The planning and marketing of the tourist attraction provide opportunities for the community to gain hope and expectations from the development of Taman Anyar Tourist Attraction in Penarungan Tourism Village, Mengwi District, Badung Regency. The problem in this research is: What is the marketing strategy for Taman Anyar Tourist Attraction as a cultural educational tourism in Penarungan Tourism Village, Mengwi District, Badung Regency? This research uses a qualitative descriptive analysis method with a phenomenological approach. The results obtained are as follows: The marketing strategy for Taman Anyar Tourist Attraction as cultural educational tourism adopts the Pentahelix model by collaborating with (1) academics, communities, the government, and media by developing flagship cultural tourism, (2) businesses, communities, and the government by developing tourism infrastructure and facilities such as accommodation and parking areas, (3) businesses, communities, and media by promoting through influencer marketing.